High iron and zinc beans: Kicking hidden hunger out of Malawi - Munthali, Justice; Fungo, Robert; Chirwa, Rowland; Onyango, Patricia; Rubyogo, Jean-Claude (Bioversity International and the International Center for Tropical Agriculture, 2020)
Two thirds (63%) of Malawian children suffer from anaemia; a condition of low haemoglobin levels in the body, and iron is a key component of haemoglobin [1]. Iron deficiency is estimated to be esponsible for half of all global anaemia cases, and iron-deficiency anaemia is a leading cause of global sickness [2]. Children suffering from iron-deficiency anaemia have poorer cognition, school achievement, and more behavioral issues into middle childhood [3].